2019
DOI: 10.1177/2192568219863805
|View full text |Cite
|
Sign up to set email alerts
|

Orthostatic Hypotension Following Cervical Spine Surgery: Prevalence and Risk Factors

Abstract: Study Design: Retrospective case series.Objectives: This study aims to determine the prevalence and risk factors for orthostatic hypotension (OH) in patients undergoing cervical spine surgery.Methods: Data was collected from records of 190 consecutive patients who underwent cervical spine procedures at our center over 24 months. Statistical comparison was made between patients who developed postoperative OH and those who did not by analyzing characteristics such as age, gender, premorbid medical comorbidities,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 21 publications
0
19
0
Order By: Relevance
“…The risk factors for postoperative OH following spine surgeries remain unclear. Neurological de cits and traumatic SCI have been reported to be associated with a higher incidence of postoperative OH (3). In our study, we found that age, sex, the number of levels instrumented and fused, whether laminectomy or osteotomy was performed during the surgery, the postoperative hemoglobin level and the postoperative albumin level were not signi cantly associated with postoperative OH following posterior spinal fusion surgeries for the correction of spinal deformities in adolescent patients.…”
Section: Discussionmentioning
confidence: 40%
See 3 more Smart Citations
“…The risk factors for postoperative OH following spine surgeries remain unclear. Neurological de cits and traumatic SCI have been reported to be associated with a higher incidence of postoperative OH (3). In our study, we found that age, sex, the number of levels instrumented and fused, whether laminectomy or osteotomy was performed during the surgery, the postoperative hemoglobin level and the postoperative albumin level were not signi cantly associated with postoperative OH following posterior spinal fusion surgeries for the correction of spinal deformities in adolescent patients.…”
Section: Discussionmentioning
confidence: 40%
“…Edward et al found that 22 of 190 patients who underwent cervical spine surgery (11.6%) developed postoperative OH. The authors found that the presence of neurological de cits is a risk factor for postoperative OH (3). The link between spinal cord injuries (SCIs) and the development of OH has been observed (15).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It is defined as a decrease in the systolic blood pressure (BP) by more than 20 mmHg or a decrease in the diastolic BP be more than 10 mmHg from the baseline BP within 3 min of changing the body position from a supine position to an upright posture [ 1 ]. Postoperative OH is a common manifestation following various surgeries, and its etiology is multifactorial and may vary according to the type of surgery [ 2 , 3 ]. Postoperative OH is often characterized by symptoms of syncope, dizziness, and light headedness.…”
Section: Introductionmentioning
confidence: 99%